Galactomannan Downregulates the Inflammation Responses in Human Macrophages via NFκB2/p100 - Víctor Toledano; Enrique Hernández-Jiménez; Carolina Cubillos-Zapata; Marta Flandez; Enrique Álvarez; Aníbal Varela-Serrano; Ramón Cantero; Gema Valles; Francisco García-Rio; Eduardo López-Collazo (Mediators of Inflammation)
We show that galactomannan, a polysaccharide consisting of a mannose backbone with galactose side groups present on the cell wall of several fungi, induces a reprogramming of the inflammatory response in human macrophages through dectin-1 receptor. The nuclear factor kappa-light-chain-enhancer of activated B cells 2 (NFκB2)/p100 was overexpressed after galactomannan challenge. Knocking down NFκB2/p100 using small interfering RNA (siRNA) indicated that NFκB2/p100 expression is a crucial factor in the progression of the galactomannan-induced refractoriness. The data presented in this study could be used as a modulator of inflammatory response in clinical situations where refractory state is required.